2012
DOI: 10.1016/j.tetlet.2012.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Ugi/Robinson–Gabriel reactions directed toward the synthesis of 2,4,5-trisubstituted oxazoles

Abstract: This Letter discloses a novel concise synthesis of a series of 2,4,5-trisubstituted oxazoles via a tandem Ugi/Robinson–Gabriel sequence. Herein, 2,4-dimethoxybenzylamine 1 was used as an ammonia equivalent in combination with arylglyoxal 3 and supporting Ugi reagents, an isonitrile and carboxylic acid. As such the product of the acid treated Ugi intermediate is ideally configured to undergo a Robinson–Gabriel cyclodehydration reaction to yield the desired oxazole scaffold 5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 52 publications
(10 reference statements)
0
9
0
Order By: Relevance
“…Thus, we performed an U‐3CR on the indole‐based imines yielding compounds 14a – e . Then, utilizing phenyl glyoxal in a Passerini reaction, we were able to synthesize compound 15 which could be transformed to a variety of derivatives . In addition, we performed a Passerini reaction with keto‐carboxylic acids affording the corresponding γ‐ and δ‐lactone derivatives 16a , b .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we performed an U‐3CR on the indole‐based imines yielding compounds 14a – e . Then, utilizing phenyl glyoxal in a Passerini reaction, we were able to synthesize compound 15 which could be transformed to a variety of derivatives . In addition, we performed a Passerini reaction with keto‐carboxylic acids affording the corresponding γ‐ and δ‐lactone derivatives 16a , b .…”
Section: Resultsmentioning
confidence: 99%
“…The conversion of Ugi product 133 to oxazole 135 was subsequently carried out via a debenzylation/ cyclodehydration protocol using (POCl 3 ), which led to the desired Robinson-Gabriel cyclodehydration reaction (Scheme 28). 75 In another interesting synthesis employing the Ugi reaction is the synthesis of aryloxazolone compounds, which are found in many potent non-steroidal drugs and found to be anti- A series of benzene/imidazole systems with more than three connected aromatic rings was synthesized using U-4CR through the condensation of terephthalic acid 44, c-hexylisocyanide 81 with n-butylamine 14, and phenylglyoxal hydrate 142 to afford Ugi adduct 143 followed by condensation with ammonia 144 to give the target compound 145 (Scheme 30). 78…”
Section: Synthesis Of Ve-membered Heterocyclic Compoundsmentioning
confidence: 99%
“…In contrast, Shaw et al [ 113 ] reported another convenient approach in which a sequential Ugi 4-CR followed by a Robinson–Gabriel reaction resulted in the desired oxazoles ( Scheme 44 ). Herein, dimethoxybenzylamine, several isocyanides, aryl-glyoxals and (hetero)-aryl carboxylic acids afforded the desired corresponding Ugi-products 144 in reasonable to good yields (42–65%).…”
Section: Reviewmentioning
confidence: 99%